(untitled) (Research, Society and Development, 2022)
The development of new antimicrobial polymeric materials is in prominence due to its versatility of applications, especially for the manufacture of active packaging food. Cellulose acetate is an example of polymeric material used to this purpose, due to its characteristics of biodegradability and easy processing, in addition its natural origin and no toxicity. Geranyl acetate is an ester derived from geraniol, which has good antimicrobial properties and good thermal stability, which makes it interesting to be applied as an antimicrobial agent, avoiding the trivial and often problematic metallic nanoparticles and also volatile essential oils. In this work, antibacterial and antifungal cellulose acetate films were obtained through the incorporation of geranyl acetate ester (in concentrations of 0.5 and 1.0% v/v), by using the casting technique. This new material was tested against gram-positive and gram-negative bacteria and fungi. Results showed that it is possible to obtain antibacterial and antifungal cellulose acetate films with the incorporation of geranyl acetate ester, with excellent antibacterial activity against gram-positive and gram-negative bacteria and good antifungal activity.